The influence of rehydration on decomposition in the Highveld region of South Africa, using a pig model - du Toit, Claire Lynne (My University, 2022)
Rainfall has been reported to influence decomposition with the timing of the precipitation, causing either an increase or decrease in decomposition rates. Researchers have observed that carcasses exposed to rainfall may re-initiate decomposition in desiccated tissue. However, no conclusive research-based evidence exists on the specific effects of rehydration on decomposition. Therefore, this study aimed to assess the effects of artificial rehydration on the rate and progression of decomposition after remains have stalled in the advanced stage of decomposition. Twelve adult pig carcasses (40-100kg) were set out in the central Highveld of South Africa during cooler (April – July 2021), and warmer (July – November 2021) climates, and decomposition was scored ±three times a week to obtain the total body score. All carcasses (8 = experimental; 4 = controls) were covered by chicken wire cages with transparent tarps to control for external factors and prevent natural rehydration. Once the experimental carcasses reached a three-visit stasis in the advanced phase of decomposition, they were artificially rehydrated, and decomposition was further observed. The trials were split into cooler and warmer deployments, and analysis of the data indicated changes in the progression and rate of decomposition between the control and experimental groups. The rehydrated experimental carcasses showed re-initiation of decay, along with insect re-colonization, while the control carcasses mainly remained in a state of stasis and insect activity ceased altogether. It was also noted that the experimental group displayed greater cadaver decomposition islands. Results indicate that both direct and indirect rehydration increases the rate of decomposition and also changes the progression thereof. Future research to further understand how rehydration (artificial and natural) impacts decomposition progression during its various stages along with invertebrate colonisation, will enhance our understanding of effects of these environmental factors have on the accuracy of post-mortem interval estimation.
A dissertation submitted in fulfilment of the requirements for the degree of Master of Medicine in Anatomical Sciences to the Faculty of Health Science, School of Anatomical Sciences,University of the Witwatersrand,Johannesburg, 2022